Distribution of Risk Factors and Mode of Delivery in Pregnant and Postpartum Women with Covid-19 - Deo Apringga Ayu Nanta; Puspita Deasy Rahmadiany; Wasis Nupikso; Andoharman Damanik; Fitria Nur Hasanah (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
In the beginning of 2020, COVID-19 widely spread from Wuhan City of China causing a global pandemic. Pregnant women are a group that is prone to suffer from this disease due to their physiology and immune response changes. In the early stages of pregnancy, COVID-19 infection has the potential to affect organ growth and fetal development. Risk factors, such as late pregnancy, obesity, diabetes mellitus, and cardiovascular disease have been found to cause more severe manifestation and can increase the risk of premature birth to abortion.  There is also a risk for vertical transmission which further endanger the postnatal outcome. The purpose of this study is to figure out the depiction of distribution of risk factors and mode of delivery in pregnant and postpartum women to better understand the major health problem that commonly found and which mode physicians preferred for safe delivery. This study uses an analytical descriptive approach with cross-sectional design in a period of April 2020 to September 2021 in Regional General Hospital Sidoarjo.. 231 respondents were selected with total sampling of the population and are based on the positive result of antigen swab and/or RT-PCR COVID-19 test and risk factor categories which has been determined. The obtained data then statistically analyzed using The IBM SPSS Statistics and described in a table. The result of this study showed that the majority of respondents are not in the risk category yet certain conditions are commonly found and C-section is preferred for delivery.